Impact of Role Self-Distance and Stagnation on Job Alienation among Managers of Public Enterprises in Nepal - Ojha, Gaurav (The International Research Journal of Management Science, 2025)
Background: This study examines the impact of role self-distance and role stagnation on job alienation experienced by managers in public enterprises of Nepal. Purpose: The main objective of this study is to investigate to what extent role stagnation and role self-distance, as negative attitudes, adversely affect the occurrences of job alienation among managers of public enterprises. Methodology: This study applies a quantitative methodology and cross-sectional survey research design together with descriptive, independent T-tests and multiple regression for data analysis with the sample size of 190 managers associated with public enterprises of Nepal. Findings: The findings from the descriptive and multi-regression analyses indicate that role stagnation has a positive and significant impact on job alienation among employees, whereas the relationship between role self-distance and job alienation is positive yet statistically insignificant. Implications: Based on the findings, this study suggests that public enterprises in Nepal need to recognize that self-efficacy of managerial-level employees has a crucial role in mitigating job-related individual alienation that arises from feelings of role self-distance and stagnation. Originality/value: It is the first of its kind research that has examined the relationship between role stagnation, role self-distance, and job alienation considering institutional characteristics of Nepalese public enterprises.